Improved Solubility and Oral Absorption of Emodin-Nicotinamide Cocrystal Over Emodin with PVP as a Solubility Enhancer and Crystallization Inhibitor - Ban, Eunmi; An, Seong Hyeon; Park, Boosung; Park, Minwoo; Yoon, Na-Eun; Jung, Byung Hwa; Kim, Aeri (ELSEVIER SCIENCE INC, 2020)
Emodin exerts anti-inflammatory and anti-cancer effects. However, its poor water solubility limits development into a pharmaceutical product. Although an emodin-nicotinamide cocrystal (ENC) with improved dissolution rate was proposed as a potential candidate, crystallization back to emodin after dissolution diminished the advantage of the cocrystal approach. The objectives of this study were to identify a crystallization inhibitor to maintain the emodin supersaturation generated by ENC dissolution, and to examine its effect on oral pharmacokinetics of ENC. Among various polymers, polyvinylpyrrolidone K30 (PVP) was the most effective solubilizer and crystallization inhibitor. The solubility of ENC in a simulated intestinal fluid containing 1.5% PVP was 2-fold higher than that of emodin. However, comparison of oral pharmacokinetics in rats between ENC and emodin did not reflect such improved solubility of ENC in vitro relative to emodin. Instead, the plasma concentrations of a major metabolite of emodin showed a positive correlation with in vitro dissolution results, suggesting rapid gastrointestinal metabolism of emodin during absorption. In conclusion, PVP contributes to enhanced dissolution rates of ENC and inhibits crystallization of emodin in vivo, so that more metabolites can be formed and absorbed. Therefore, a metabolism inhibitor would be necessary to improve the oral bioavailability of emodin further. (C) 2020 American Pharmacists Association (R). Published by Elsevier Inc. All rights reserved.
Keywords: STABILITY; SUPERSATURATION; PRECIPITATION; DISPERSIONS; MEDIA